REMOVAL OF DAIRY EFFLUENT CHEMICAL OXYGEN DEMAND (COD) - P.ASHOK KUMAR; P.BANGARAIAH; G.PRABHAKAR (International Journal of Pharma and Bio Sciences, 2014)
The environmental problem is the major concern for any industry and there is a great need to that along green lines. Dairy is being one of the most important food industries in India, they produce wide spectrum of milk products. After the MIF treatment the Chemical Oxygen Demand (COD) levels of dairy effluent water were found to be around 900 ppm. By employing various surface active materials like ferric chloride, alum and commercial coal the COD levels are minimized to the required level stipulated by the environmental standards and the effect of various parameters on COD levels during the treatment are evaluated. Initial and final COD levels were determined before and after the treatment. Open reflux method is used for determining the characteristics of COD levels.